The effect of oral N-acetylcysteine on serum high sensitive CRP and plasma hemoglobin levels in end-stage renal disease patients under routine hemodialysis; a randomized placebocontrolled clinical trial - Bahman Bashardoust; Roya Alaei; Sousan Mohammadi Kebar; Sabah Hasani; Afshin Habibzadeh (Society of Diabetic Nephropathy Prevention, 2018)
Background: Oxidative stress and systemic inflammation is increased in end-stage renal disease (ESRD) patients. Due to the various effects of oxidative stress in ESRD patients, different antioxidants have been evaluated. Objectives: In this study, we evaluated the effect of oral N-acetylcysteine (NAC) as an antioxidant on the serum high-sensitive C-reactive protein (hs-CRP) and plasma hemoglobin levels in the ESRD patients who were under routine hemodialysis. Patients and Methods: In this randomized placebo-controlled clinical trial, 51 ESRD patients under routine hemodialysis were randomly assigned to receive NAC 1200 mg daily for 1 month (n=26) or placebo (n=25). Laboratory findings including hemoglobin, ferritin, hsCRP were measured in patients before and after treatment. Results: NAC group compared to placebo group had significantly higher ferritin levels before treatment (p=0.02) and lower phosphorus levels after treatment (p=0.03). Comparing the results before and after treatment in each group, a significant reduction in hematocrit (p=0.002), ferritin (p=0.006), hs-CRP (p=0.02) and an increase in alkaline phosphatase levels (p=0.005) in NAC group and significant reduction in calcium levels (p<0.001) in placebo group was detected. No major side effects were seen. Conclusions: One month treatment with oral NAC resulted in reduced levels of hematocrit, ferritin and Hs-CRP, indicative of role of NAC in controlling inflammation in ESRD patients under hemodialysis. However, NAC was not effective in treatment of anemia, although the treatment duration was low.